2017
DOI: 10.15740/has/ijpp/10.1/140-145
|View full text |Cite
|
Sign up to set email alerts
|

Rhizome rot of ginger-management through non-chemical approach

Abstract: Ginger (Zingiber officinale Rosc.) an important spice crop grown in different states of India especially Himachal Pradesh, a hilly area situated in northern Himalayas. Pythium and Fusarium are the main fungus which affect the crop in a drastic manner. Ginger rhizome diseases are both rhizome seed and soil borne and their chemical management leads to notorious effect on environment and ecosystem. Therefore, an attempt to work out for isolation of Pythium and Fusarium sp. (major pathogens causing ginger rot) fro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 3 publications
0
1
0
Order By: Relevance
“…This method not only helps to improve soil properties but also helps to check for soil-borne diseases. Soil amendments with the cakes made from Azadirachta indica, Calophyllum inophyllum, or Pongamia glabracan reduce ginger rhizome rot caused by Pythium aphanidermatum and Fusarium solani (Thakore et al 1987). A similar observation was also reported in the incidence of rhizome rot by Pythium sp.…”
Section: Soil Solarization and Organic Amendmentsupporting
confidence: 74%
“…This method not only helps to improve soil properties but also helps to check for soil-borne diseases. Soil amendments with the cakes made from Azadirachta indica, Calophyllum inophyllum, or Pongamia glabracan reduce ginger rhizome rot caused by Pythium aphanidermatum and Fusarium solani (Thakore et al 1987). A similar observation was also reported in the incidence of rhizome rot by Pythium sp.…”
Section: Soil Solarization and Organic Amendmentsupporting
confidence: 74%
“…Turmeric rhizome yields were found significantly highest (42.71 t•ha -1 ) in the treatment applying vermicompost along with synthetic fertilizers in southern India (Isaac & Varghese 2016). Similarly, some studies found that various Trichoderma species are effective to manage rhizome rot disease in ginger and turmeric (Bharathi & Sudhakar 2011;Acharya et al 2016;Thakur et al 2017).…”
Section: Discussionmentioning
confidence: 99%